The Role of Waqf In The Classic Islamic Education Period - Maralottung Siregar (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Waqf is said to be a virtue, because waqf is the surrender of property for social purposes, the purpose of which is not solely to get closer (taqarrub) to Allah SWT in order to get a reward from Him, but this waqf donation is worth continuous. This study aims to determine the role of waqf during the classical Islamic education period. This type of research is library research. The results of this study are : education during the heyday of classical Islam was not due to very large financial support from the government but due to the large participation of the community in supporting the development of science, especially in terms of funding, which was manifested in the form of endowments. If the cost of education can be covered by funds raised from waqf then Islamic education will be better in the future, therefore waqf must be managed professionally in the framework of advancing Islamic education in the future. Waqf as a financial supporter of the implementation of classical Islamic education, places a large role of waqf which functions as a financial support, to the implementation of education during the classical Islamic period, there is a very clear relationship. The needs in the world of education at that time were fulfilled properly by waqf